Nanotubes from the Misfit Layered Compound (SmS)1.19TaS2 Atomic Structure, Charge Transfer, and Electrical Properties - Sreedhara, M B (Chemistry of materials : a publication of the American Chemical Society, 2022)
© 2022 The Authors. Published by American Chemical Society.